P018 Anti-carbamylated protein antibodies as a clinical response predictor in rheumatoid arthritis patients treated with abatacept. (March 2019) - Fredi, M; Boldini, M; Kumar, R; Piantoni, S; Cavazzana, I; Garrafa, E; Bazzani, C; Tincani, A; Franceschini, F
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: The presence of anti-carbamylated protein antibodies (anti-CarP) has been detected in rheumatoid arthritis (RA). 1 Anti-CarP autoAbs target proteins that are modified through an irreversible post-translational modification named carbamylation. Objectives: The aim of this work was to assess whether anti-CarP antibodies can be used as a predictive factor of clinical response to abatacept. Methods: Peripheral blood samples of selected patients were collected at the beginning of the therapy with abatacept (T0) and every six months for one year (T6 and T12). A home-made ELISA was applied to determine serum anti-CarP levels. Commercial anti-citrullinated protein antibodies (anti-CCP3) (Inova Diagnostic), Rheumatoid Factor (RF) (Siemens) and high sensitivity C reactive protein (hsCRP) were also tested. Results: Sixty RA patients (49 female (81.2%)), all caucasian, treated with abatacept were enrolled. Fifty-three (88.3%) and fifty-six (93.3%) patients were also treated with corticosteroids and synthetic DMARD respectively. At baseline anti-CarP antibodies were found in 18 (30%) patients; RF and anti-CCP were positive in 35 (58%) and 51 (85%) patients respectively. Comparing anti-CarP+ with anti-CarP- patients at T0, anti-CarP+ group resulted younger (p<0.01) and with a longer disease duration (p<0.05); hsCRP was higher in anti-CarP+ group (p<0.05). Considering the entire cohort, a significant reduction of anti-CarP titre at T6 and T12 of treatment was shown (p<0.0001) while anti-CCP and RF titre did not show any significant change. Thirteen out of 18 patients anti-CarP+ were available for analysis at T6 and in 6 cases turned anti-CarP-. A significant reduction of DAS28-CRP at T6 was found in the subgroup of anti-CarP+ pts in comparison with the negative ones (p=0.03). No significant results were found dividing the cohort using the positivity to anti-CCP and/or RF. Furthermore, stratifying groups of patients for the combination of biomarkers, any groups including anti-CarP+ resulted in a trend towards a higher DAS28 reduction compared with the combination of anti-CCP+ and RF+ and anti-CAP- ones. Conclusions: The precocious onset and a longer disease duration in anti-CarP positive patients might suggest them as a specific risk factors for RA in this subgroup of patients. The link between the anti-CarP positivity at baseline and the higher reduction of disease activity during the first six months of treatment permitted us to hypothesize that anti-CarP antibodies, but not anti-CCP and/or RF, could be a predictive factor of a good clinical response to abatacept. Reference: Shi J, et al. Proc Natl Acad Sci USA 2011;108(42):17372–7. Disclosure of Interest: None declared.